PERSPECTIVE FROM THE FIELD: Innovative Geographic Visualization for Improved Understanding and Effective Public Participation in Environmental Policy Making and Implementation. (22nd April 2016) - Arun Kumar, A; Upgupta, Sujata; Gaur, Tanvi; Sathyakumar, S.; Ramesh, K.
Abstract : Public participation can not only contribute to improvement of decisions, but can also help in enhancing the capability of communities to solve problems and pursue common concerns. Arguably, a strong public participation in environmental governance could increase the commitment among stakeholders, which strengthens the compliance and enforcement of policies. Nevertheless, despite the critical importance of public participation in policy making, such involvements are not as effective as may be desired for logical conclusion and efficient implementation of policies. The near nonexistence of visualization tools at the disposal of the general public to aid in visual understanding of the problem is the major cause factor for the non-involvement and negligible influence of the populace in policy making. One such facility is being established at Wildlife Institute of India for visualizing the impacts of climate change on biodiversity of Indian Himalayan Region (IHR). Environmental Practice 18: 129–131 (2016)